(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
This paper examines the rhetoric of post-colonial mentality, mindset and attitude in Jean Rhys’s novel Wide Sargasso Sea and looks at how the writer is not aloof from the colonial mindset. Drawing on insights and postulations from Gayatri Spivak’s post-colonialism and Lee Erwin’s new-historicism, this article analyzes the imperial discourse in the novel. Although the writer shows her narrator being close to black people as a Creole woman, the writer’s closeness to the imperial mindset is evident throughout the novel. This paper concludes that by creating a certain distance from the ex-slaves, the writer is not able to fully liberate herself from her imperial mindset. Although the writer tries to affiliate herself with the ex-slaves, she however remains within her own culture, that is, culture of Creole.